2012
DOI: 10.5301/jabfm.2012.9255
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Adhesive Agents on the Shear Bond Strength of a Self-Adhesive Resin Cement

Abstract: RelyX Unicem may be preferable in many cases because of its simplified application and reduced technique-sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…It is important to establish differences between the methodology to test the bond strength. Studies showed high values for shear bond strength until 445 MPa [21]. Microtensile bond strength tests show values in general in order from 6 to 67 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to establish differences between the methodology to test the bond strength. Studies showed high values for shear bond strength until 445 MPa [21]. Microtensile bond strength tests show values in general in order from 6 to 67 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…The adequate selection of the adhesive system furthermore allows to take advantage of all the advantages offered by an indirect treatment [6,7,8,14,18,19,20]. For example, when the adhesive process is successful, the cementation allows a greater fracture resistance of the ceramic materials facilitated by the impregnation of the cement in the irregularities of the internal surface of the restoration and, in turn, promotes greater bonding strength and inhibits propagation of possible fissures [11,17,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, SBS between ceramic and tooth is known to be dependent on adhesive types. 32,33 The color masking ability and flexural strength of ceramics are noted to be also influenced by their thickness. 27,29,30 In addition, failures located between the dentin surfaces and bonding agent are due to the adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the other similar studies. Pekperdahci et al also recommended RelyX Unicem for its easier and faster application technique and low technique sensitivity ( 22 ). Similar results were reported by Hikita et al, who observed that there were no differences between the application of self-adhesive and total etch luting cements ( 3 ).…”
Section: Discussionmentioning
confidence: 99%